Faunal Assemblages From Lower Bed I (Oldupai Gorge, Tanzania) - Akuku, Pamela; Saladié, Palmira; Mohamed, Abdallah; Mwambwiga, Aloyce; Bushozi, Pastory; Mercader, Julio (Frontiers in Ecology and Evolution, 2022)
Palaeobiological and archeological excavations at the site of Ewass Oldupa, found in the western Plio-Pleistocene rift basin of Oldupai Gorge (also Olduvai Gorge), Tanzania, revealed rich fossiliferous levels and the earliest remains of human activity at Oldupai Gorge, dated to 2 million years ago. This paper provides zooarchaeological taxonomic, taphonomic, and behavioral analyses, applying several methods to explore the setting in which the assemblage was formed. We identified agency behind bone surface modifications, such as cut, tooth and percussion marks, and determined the frequency of carnivore tooth marks as well as their distribution on both discrete specimens and across species. In addition, our work revealed co-occurrence of modifications to include butchering marks and carnivore tooth marks. Ravaging levels were estimated as percentage. The faunal accumulation from Ewass Oldupa contains two cut marked specimens, together with low degrees of percussion and carnivore tooth marks, moderate ravaging, and diagenetic changes suggestive of water flow. Thus, multiple lines of evidence indicate a palimpsest accumulation. Taxonomic diversity is high, with up to 22 taxa representing diverse habitats, ranging from open grassland to wooded bushlands, as well as moist mosaics during Bed I. Overall, this archaeo-faunal assemblage speaks to increased behavioral versatility among Oldowan hominins and interactions with the carnivore guild.